Redirecting therapeutic T cells against myelin-specific T lymphocytes using a humanized myelin basic protein-HLA-DR2-zeta chimeric receptor. - Moisini, I; Nguyen, P; Fugger, L; Geiger, T (2008)
Therapies that Ag-specifically target pathologic T lymphocytes responsible for multiple sclerosis (MS) and other autoimmune diseases would be expected to have improved therapeutic indices compared with Ag-nonspecific therapies. We have developed a cellular immunotherapy that uses chimeric receptors to selectively redirect therapeutic T cells against myelin basic protein (MBP)-specific T lymphocytes implicated in MS. We generated two heterodimeric receptors that genetically link the human MBP84-102 epitope to HLA-DR2 and either incorporate or lack a TCRzeta signaling domain. The Ag-MHC domain serves as a bait, binding the TCR of MBP-specific target cells. The zeta signaling region stimulates the therapeutic cell after cognate T cell engagement. Both receptors were well expressed on primary T cells or T hybridomas using a tricistronic (alpha, beta, green fluorescent protein) retroviral expression system. MBP-DR2-zeta-, but not MBP-DR2, modified CTL were specifically stimulated by cognate MBP-specific T cells, proliferating, producing cytokine, and killing the MBP-specific target cells. The receptor-modified therapeutic cells were active in vivo as well, eliminating Ag-specific T cells in a humanized mouse model system. Finally, the chimeric receptor-modified CTL ameliorated or blocked experimental allergic encephalomyelitis (EAE) disease mediated by MBP84-102/DR2-specific T lymphocytes. These results provide support for the further development of redirected therapeutic T cells able to counteract pathologic, self-specific T lymphocytes, and specifically validate humanized MBP-DR2-zeta chimeric receptors as a potential therapeutic in MS.